Can't take my eyes off you attentional adhesion to mates and rivals. [article]. - Maner, Jon K.
In 3 experiments, mating primes interacted with functionally relevant individual differences to guide basic, lower order social perception. A visual cuing method assessed bias in attentional adhesion-a tendency to have one's attention captured by particular social stimuli. Mate-search primes increased attentional adhesion to physically attractive members of the opposite sex (potential mates) among participants with an unrestricted sociosexual orientation but not among sexually restricted participants Studies 1 and 2). A mate-guarding prime increased attentional adhesion to physically attractive members of one's own sex (potential rivals) among participants who were concerned with threats posed by intrasexual competitors but not among those less concerned about such threats (Study 3). Findings are consistent with a functionalist approach to motivation and social cognition and highlight the utility of integrating evolutionary and social cognitive perspectives.